High Power Ho:YAP Laser With 107 W of Output Power at 2117 nm - Jinwen Tang; Enhao Li; Fei Wang; Weichao Yao; Chongfeng Shen; Deyuan Shen (IEEE Photonics Journal)
A high power Ho:YAP laser in-band pumped by a home-constructed Tm doped all fiber master oscillator power amplifier (MOPA) is reported. The optically polished and uncoated Ho:YAP laser yielded over 107 W of output power at ∼2117.1 nm with 215.4 W of absorbed pump power, corresponding to a slope efficiency of 50.6% with respect to the absorbed pump power. The beam quality M2 parameter was measured at 80 W of output power to be ∼3.2 and ∼2.6 in x- and y-directions, respectively.